Accelerated, but not conventional, radiotherapy of murine B-cell lymphoma induces potent T cell–mediated remissions - Dutt, Suparna (Blood Adv, 2018)
Conventional local tumor irradiation (LTI), delivered in small daily doses over several weeks, is used clinically as a palliative, rather than curative, treatment for chemotherapy-resistant diffuse large B-cell lymphoma (DLBCL) for patients who are ineligible for hematopoietic cell transplantation. Our goal was to test the hypothesis that accelerated, but not conventional, LTI would be more curative by inducing T cell–mediated durable remissions. We irradiated subcutaneous A20 and BL3750 lymphoma tumors in mice with a clinically relevant total radiation dose of 30 Gy LTI, delivered in 10 doses of 3 Gy over 4 days (accelerated irradiation) or as 10 doses of 3 Gy over 12 days (conventional irradiation). Compared with conventional LTI, accelerated LTI resulted in more complete and durable tumor remissions. The majority of these mice were resistant to rechallenge with lymphoma cells, demonstrating the induction of memory antitumor immunity. The increased efficacy of accelerated LTI correlated with higher levels of tumor cell necrosis vs apoptosis and expression of “immunogenic cell death” markers, including calreticulin, heat shock protein 70 (Hsp70), and Hsp90. Accelerated LTI–induced remissions were not seen in immunodeficient Rag-2(−/−) mice, CD8(+) T-cell–depleted mice, or Batf-3(−/−) mice lacking CD8α(+) and CD103(+) dendritic cells. Accelerated, but not conventional, LTI in immunocompetent hosts induced marked increases in tumor-infiltrating CD4(+) and CD8(+) T cells and MHCII(+)CD103(+)CD11c(+) dendritic cells and corresponding reductions in exhausted PD-1(+)Eomes(+)CD8(+) T cells and CD4(+)CD25(+)FOXP3(+) regulatory T cells. These findings raise the possibility that accelerated LTI can provide effective immune control of human DLBCL.